Simulation soil water–salt dynamics in saline wasteland of Yongji Irrigation Area in Hetao Irrigation District of China - Chengfu Yuan (IWA Publishing, 2021)
In order to explore the regional water–salt balance mechanism in Hetao Irrigation District, field experiments were conducted in 2018 and 2019 in the Heji canal study area. The SWAP model was calibrated and validated based on field experiments' observed data. The SWAP model was used to simulate soil water–salt dynamics in saline wasteland after calibration and validation. The results showed that model simulation results of soil water content and soil salt concentration agreed well with the measured values. Soil water content and soil salt concentration changed obviously under the effect of farmland irrigation in the crop growing period. Soil salt was accumulated in saline wasteland. The soil salt accumulation of each soil layer in saline wasteland was 0.164, 0.092, −0.890 and −1.261 mg/cm3, respectively. Soil water content gradually increased and soil salt concentration gradually decreased in the autumn irrigation period. Soil salt was leached in the saline wasteland. The soil salt accumulation of each soil layer in the saline wasteland was −1.011, −1.242, −1.218 and −1.335 mg/cm3, respectively. The saline wasteland became a drainage and salt drainage region for cultivated land. The saline wastelands had an obvious role in adjusting salt balance and maintaining salt dynamic balance in Hetao Irrigation District. HIGHLIGHTS Soil water–salt transport is concentrated in saline wasteland.; Soil water content and soil salt concentration changed obviously in crop growing period.; Soil salt was accumulated in saline wasteland in crop growing period.; Soil water content gradually increased and soil salt concentration gradually decreased in autumn irrigation period.; Saline wasteland became a drainage and salt drainage region.;